Pelatihan Menulis “Descriptive Text” di Kelurahan Manguharjo Kecamatan Mayangan Kota Probolinggo - Utami Ratna Swari (Abdi Panca Marga, 2020)
This community service was a training in writing descriptive text for junior high school students in Joboan village, Probolinggo city. The method of this community service covered four stages: a) analyzing, b) planning and developing the content, c) implementing and d) training. In analyzing stage, the writer found problems faced by the students in writing descriptive text. In planning and developing the content stage, the writer developed method to write descriptive text by utilizing picture and guided question. With this pandemic situation, in implementing stage, the writer gathered 10 participants by applying health protocol suggested by the Government. Training stage was done for three days, 20-22 of July 2020. In the first day, the writer gave explanation related descriptive text. In the second day, the participants started to practice writing descriptive text by using picture and guided question. Feedback was given in the third day. The results of this training were shown by the presence of all participants three days in a row, they also gave responds and asked questions enthusiastically in the training process. The participants no longer faced difficulty in writing descriptive text since they knew that picture and guided question can help them write descriptive text better. Keywords: training, writing, descriptive text, picture, guided question, feedback